Environmentally friendly precursor and cathode material for lithium-ion batteries and method for producing the same

JP7652799B2Active Publication Date: 2025-03-27XTC NEW ENERGY MATERIALS(XIAMEN) LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022573494
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-04
Filing Date
2021-03-26
Publication Date
2025-03-27
Estimated Expiration
2041-03-26

Smart Images

  • Figure 0007652799000002
    Figure 0007652799000002
  • Figure 0007652799000003
    Figure 0007652799000003
  • Figure 0007652799000001
    Figure 0007652799000001
Patent Text Reader

Abstract

The present invention relates to an environmentally friendly precursor and a cathode material for lithium-ion batteries, and a method for preparing the same. The method for preparing the environmentally friendly precursor includes: subjecting a metal and / or metal oxide, an oxidant, water, and a complexing agent to a chemical corrosion crystallization reaction under conditions of a conductivity of ≥ 200 μS / cm, an ORP of ≤ 100 mV, and a complexing agent concentration of 3-50 g / L; magnetically separating the resulting reaction product after the reaction to obtain magnetic particles and a slurry; further subjecting the slurry to solid-liquid separation to obtain solid particles and a filtrate; and then washing and drying the solid particles. The precursor prepared using the method of the present invention produces no wastewater during the dissolution and crystallization process and consumes water continuously, thereby achieving environmental friendliness and effectively improving the initial charge / discharge efficiency of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the field of materials, and relates to an environmentally friendly precursor and positive electrode material for lithium ion batteries and a method for preparing the same. [Background technology]

[0002] With the application of lithium-ion batteries in electric vehicles, the positive electrode material of lithium-ion batteries has attracted widespread attention, and the performance of the positive electrode material of lithium-ion batteries directly affects the use and popularity of electric vehicles. The development of high-capacity, high-safety, long-life, low-cost and environmentally friendly positive electrode material of lithium-ion batteries is the main direction of future development. Currently, there are many kinds of materials coexisting in vehicle positive electrode materials, and lithium iron phosphate, multi-component materials, and lithium manganese oxide are all currently used in the EV field. Here, Panasonic of Japan and LG of Korea have already successfully applied high-nickel materials to electric vehicles in large quantities, but due to the shortcomings of the multi-component materials themselves, there is still room for improvement in terms of safety performance, high capacity, high multiplication rate, long cycle performance, etc.

[0003] With the rapid development of lithium-ion batteries, the requirements for battery materials are increasing, especially for the uniformity of the material components and phase structure. The performance of battery materials directly affects the electrical performance of the battery. In order to improve the performance of materials, the structural defects of materials are currently being studied by improving the structural performance of precursors. Under the condition of pH value of 6-12, H in the solution +The conventional process cannot use metal elemental and / or metal oxide as raw material to produce metal hydroxide precursor because the concentration is generally low and the metal elemental and / or metal oxide as raw material cannot be used to carry out redox reaction in the manner of proton conduction. The method for producing precursor according to the purpose generally adopts co-precipitation crystallization technology, specifically, metal salt solution and hydroxide are added in parallel flow to a stirring reactor to carry out mixed precipitation, a large amount of sulfate after co-precipitation crystallization is left in the mother liquor, and ammonia water is added to the precipitation system as a complexing agent, and ammonia is finally retained in the reaction system in the form of ammonium salt, and after solid-liquid separation, the mother liquor part containing ammonia, ammonium salt and sulfate in the solid precursor is removed, and some heavy metals and small solid particles are also dissolved in the mother liquor. Therefore, the conventional co-precipitation crystallization technology not only requires the consumption of a large amount of materials such as hydroxide and ammonia, but also generates a large amount of exhaust gas, wastewater and waste, which causes a large burden on the environment. In addition, the initial charge and discharge efficiency of lithium ion batteries corresponding to the precursor obtained by adopting the conventional co-precipitation crystallization technology is low, and there is still room for improvement. Summary of the Invention [Means for solving the problem]

[0004] The object of the present invention is to provide an environmentally friendly precursor and a positive electrode material for a lithium ion battery which improves the initial charge / discharge efficiency of the lithium ion battery and does not burden the environment, in order to overcome the defects of the low initial charge / discharge efficiency of the lithium ion battery corresponding to the precursor obtained by the conventional coprecipitation crystallization method and which causes a large burden on the environment, and a manufacturing method thereof.

[0005] As mentioned above, under conditions of pH value of 6 to 12, H in the solution +Conventional processes cannot use metal elemental and / or metal oxide as raw materials to produce precursors because the concentration is generally low and the redox reaction cannot be carried out in the manner of proton conduction using metal elemental and / or metal oxide as raw materials. After extensive research, the inventors of the present invention have found that the mass transfer rate of the solution can be accelerated by placing metal and / or metal oxide, oxidant, water and complexing agent under the conditions of electrical conductivity ≧200uS / cm, oxidation-reduction potential ORP value ≦100mv and complexing agent concentration of 3-50g / L, and H + can destroy the interfacial film formed on the surface of metal and / or metal oxide, so that the liquid-solid interfacial film realizes electronic conduction and generates electrochemical corrosion on the surface of solid metal and / or metal oxide, solving the oxidation-reduction reaction that cannot be realized by conventional chemical reactions, and can refine the primary particle morphology of particles, so that the internal structure of the obtained precursor is more uniform, and the initial charge-discharge efficiency is higher after sintering into a positive electrode material for lithium ion batteries. Based on this, the present invention is completed.

[0006] Specifically, the present invention provides an environmentally friendly method for preparing a precursor, which includes: carrying out a chemical corrosion crystallization reaction of a metal and / or metal oxide, an oxidant, water and a complexing agent under the conditions of electrical conductivity≧200uS / cm, an oxidation-reduction potential ORP value≦100mv, and a complexing agent concentration of 3-50g / L; magnetically separating the reaction product obtained after the reaction is completed to obtain magnetic particles and a slurry; further separating the slurry into solid and liquid to obtain solid particles and a filtrate; and then washing and drying the solid particles to obtain a precursor.

[0007] In the present invention, the metals and / or metal oxides are converted to the corresponding metal hydroxides after undergoing chemical corrosion crystallization reaction, i.e., Me→Me n+ +ne, MexOy → Me n++(n-2x / y)e. The oxidizing agent and water are raw materials involved in the oxidation reaction of metals and / or metal oxides, and the amount of both is enough to convert the metals and / or metal oxides into the corresponding metal hydroxides. The addition of the oxidizing agent creates conditions for the dissolution and coprecipitation of the metals and / or metal oxides, which then dissolve and crystallize to obtain metal hydroxides. In the chemical corrosion crystallization reaction process, water is involved in the reaction as a raw material to convert the metals and / or metal oxides into hydroxides, and the crystallization process does not consume water constantly and does not produce excess wastewater, thereby achieving the purpose of being environmentally friendly in the crystallization process.

[0008] Specific examples of the metal and / or metal oxide include, but are not limited to, at least one of the metals and their metal oxides, such as nickel, cobalt, manganese, aluminum, zirconium, tungsten, magnesium, strontium, and yttrium, and the above metals and / or metal oxides can be arbitrarily adjusted from 0 to 100% according to actual needs. In addition, the metal and / or metal oxide is preferably used in the form of an amorphous, coarse powder, which can improve the reaction rate and shorten the reaction time.

[0009] In a preferred embodiment, the metals and / or metal oxides are used in the following forms: Ni-Co-Mn-Zr-W, Ni-Mg-Zr-W, Co-Al-Mg-Ti, or Ni-Co-Al-Zr-Ti. Here, the molar ratio of Ni, Co, Mn, Zr, and W in Ni-Co-Mn-Zr-W is 1:(0.05-1):(0.1-1):(0-0.2):(0-0.2). The molar ratio of Ni, Mg, Zr, and W in Ni-Mg-Zr-W is 1:(0.001-0.1):(0.001-0.1):(0.001-0.1). The molar ratio of Co, Al, Mg, and Ti in Co-Al-Mg-Ti is 1:(0.001-0.1):(0.001-0.1):(0-0.1). The molar ratio of Ni, Co, Al, Zr and Ti in Ni-Co-Al-Zr-Ti is 1:(0.001-0.5):(0.001-0.1):(0-0.1):(0-0.1). When Ni-Co-Mn-Zr-W or Ni-Mg-Zr-W is used, the lithium ion battery corresponding to the obtained precursor has higher high-temperature cycle performance and initial charge-discharge efficiency. When Co-Al-Mg-Ti is used, the lithium ion battery corresponding to the obtained precursor has higher voltage cycle performance. When Ni-Co-Al-Zr-Ti is used, the lithium ion battery corresponding to the obtained precursor has higher high-temperature cycle performance and high safety performance. In the above combination, each metal may be used in the form of a single metal, in the form of a metal oxide, or in the form of a mixture of both.

[0010] Specific examples of the oxidizing agent include, but are not limited to, at least one of nitric acid, oxygen, air, sodium chlorate, potassium permanganate, and hydrogen peroxide, and preferably nitric acid. When nitric acid is used as the oxidizing agent, ammonia gas is generated as the reaction product, and at this time, no complexing agent needs to be added or a small amount of complexing agent can be added to meet the concentration requirement.

[0011] The function of the complexing agent is to complex the metal ions formed by the chemical corrosion crystallization reaction, and to reduce the supersaturation coefficient of the system. Specific examples of the complexing agent include, but are not limited to, at least one of ammonia water, ammonium sulfate, ammonium chloride, ethylenediaminetetraacetic acid, and ammonium nitrate. The concentration of the complexing agent is 3 to 50 g / L, and may be, for example, 3 g / L, 5 g / L, 10 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L, 50 g / L, etc.

[0012] The chemical corrosion crystallization reaction is carried out under the condition of electrical conductivity ≧200uS / cm, preferably 200 to 50000uS / cm. The electrical conductivity is, for example, 200uS / cm, 300uS / cm, 400uS / cm, 500uS / cm, 600uS / cm, 700uS / cm, 800uS / cm, 900uS / cm, 1000uS / cm, 1100uS / cm, 1200uS / cm, 1300uS / cm, 1400uS / cm, 1500uS / cm, 1600uS / cm, 1700uS / cm, 200uS / cm, 2100uS / cm, 2200uS / cm, 2300uS / cm, 2400uS / cm, 2500uS / cm, 2600uS / cm, 2700uS / cm, 2800uS / cm, 2900uS / cm, 3000uS / cm, 3100uS / cm, 3200uS / cm, 3300uS / cm, 3400uS / cm, 3500uS / cm, 3600uS / cm, 3700uS / cm, 3800uS / cm, 3900uS / cm, 4000uS / cm, 4100uS / cm, 4200uS / cm, 4300uS / cm, 4400uS / cm, 4500uS / cm, 4600uS / cm, 4700uS / cm, 4800uS / cm, 4900uS / cm, 5000uS / cm / cm, 1800uS / cm, 1900uS / cm, 2000uS / cm, 3000uS / cm, 4000uS / cm, 5000uS / cm, 10000uS / cm, 15000uS / cm, 20000uS / cm, 25000uS / cm, 30000uS / cm, 35000uS / cm, 45000uS / cm, 50000uS / cm, etc. When the conductivity of the chemical corrosion crystallization reaction is controlled within the above range, the mass transfer rate is accelerated and H + can destroy the interfacial film formed on the surface of the metal and / or metal oxide, so that the oxidation-reduction reaction proceeds smoothly and the metal and / or metal oxide is converted into the corresponding metal hydroxide. The conductivity can be controlled by adding a salt to the reaction system. Specific examples of the salt include, but are not limited to, at least one of sulfate, chloride and nitrate of sodium and / or lithium, specifically at least one selected from sodium sulfate, sodium chloride, sodium nitrate, lithium sulfate, lithium chloride and lithium nitrate.

[0013] The chemical corrosion crystallization reaction is carried out under the condition of an ORP value ≦100mv, preferably −1000mv to 100mv. The ORP value may be, for example, −1000mv, −900mv, −800mv, −700mv, −600mv, −500mv, −400mv, −300mv, −200mv, −100mv, 0mv, 100mv, etc. If the ORP value is controlled within the above range, electrochemical corrosion of the liquid-solid interface film can be realized and the crystallization of the metal hydroxide can be promoted. The ORP value can be controlled by a combination of the conductivity and the ammonia and / or ammonium concentration in the reaction system. In the present invention, the ORP value is measured by a Mettler Toledo S220 multi-parameter tester.

[0014] The chemical corrosion crystallization reaction may be a continuous reaction or a batch reaction. In a preferred embodiment, the chemical corrosion crystallization reaction process has an input power of 0.1 to 1.0 kW / m. 2 ·h, the metal ion concentration in the reaction system is 1-30g / L, the complexing agent concentration is 3-50g / L, the pH value is 6-12, the reaction temperature is 20-90°C, and the reaction time is 10-150h. Here, by controlling the stirring intensity, the metal ion concentration in the reaction system, the complexing agent concentration, the pH value, the reaction temperature, etc., the particle size of the precursor can be controlled to be between 2 and 30μm.

[0015] The magnetic separation may be a batch type magnetic separation or a continuous type magnetic separation. The strength of the magnetic separation is preferably 100 to 5000 Gas.

[0016] In a preferred embodiment, the environmentally friendly precursor manufacturing method provided by the present invention further includes returning all of the magnetic particles, filtrate and washing water to the chemical corrosion crystallization reaction system to replenish the water consumed during the crystallization process, thereby realizing the closed circulation and full use of the materials, and no waste water is discharged during the crystallization process, thereby realizing environmental friendliness.

[0017] The present invention further provides an environmentally friendly precursor produced by the above method.

[0018] The present invention further provides a method for producing a cathode material for a lithium ion battery, the method comprising: (1) employing the above method to produce an environmentally friendly precursor; (2) mixing the environmentally friendly precursor with a lithium source, followed by calcination to obtain a positive electrode material for a lithium ion battery.

[0019] In a preferred embodiment, in step (2), the Li / Me molar ratio of the environmentally friendly precursor and the lithium source is (0.9-1.3):1.

[0020] In a preferred embodiment, in step (2), the firing conditions include a temperature of 600 to 1100° C., a time of 5 to 40 hours, and a firing atmosphere of air or oxygen.

[0021] In a preferred embodiment, in step (2), the lithium source is at least one selected from lithium hydroxide, lithium acetate, lithium nitrate, lithium sulfate, and lithium bicarbonate.

[0022] The present invention further provides a positive electrode material for a lithium ion battery produced by the above method.

[0023] The present invention breaks through the conventional co-precipitation crystallization technology of metal salt solution and hydroxide, and uses metal and / or metal oxide, oxidant, water and complexing agent to carry out chemical corrosion crystallization reaction at a specific conductivity, oxidation-reduction potential ORP value and complexing agent concentration to prepare a precursor, the fine particle morphology and uniform internal structure of which provide a good basis for improving the initial charge-discharge efficiency of lithium ion batteries.In addition, the precursor is prepared by the method provided by the present invention, which does not generate wastewater during the dissolution and crystallization process and consumes water continuously, thereby achieving the purpose of being environmentally friendly. [Brief description of the drawings]

[0024] [Figure 1] FIG. 1 is a scanning electron microscope photograph of the environmentally friendly precursor obtained in Example 1. [Diagram 2] FIG. 2 is a scanning electron microscope photograph of the composite oxide powder obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The present invention will be described in detail below with reference to examples. EXAMPLES

[0026] (1) Metal mixture (five metals of Ni, Co, Mn, Zr and W are mixed in a molar ratio of 1:1:1:0.03:0.05), nitric acid, high purity water and sodium sulfate are added to the reactor in a parallel flow at a molar ratio of 10:1:1:1 to carry out a chemical corrosion crystallization reaction. At the same time, 10 g / L of ammonium sulfate is added. Under normal pressure conditions, the oxidation-reduction potential ORP value is controlled to -1000 mv, the conductivity is controlled to 200 uS / cm, and the stirring input power is 1 kW / m. 3 ·h, metal ion concentration is controlled at 5g / L, pH value is controlled at 6-8, reaction temperature is controlled at 20℃, residence time of material in reactor is controlled at 30h, water is consumed continuously during crystallization process, no extra waste water is generated, magnetic separation is performed at 100Gas magnetic separation intensity to obtain magnetic particles and slurry after sufficient reaction, solid particles and filtrate are obtained by solid-liquid separation of the slurry, solid particles are washed and dried to obtain precursor, magnetic particles, filtrate and washing water are returned to the reactor for further reaction, and water consumed during crystallization process is replenished. The scanning electron microscope (SEM) image of the precursor is shown in FIG. 1. As can be seen from FIG. 1, the precursor particles are uniformly distributed, spherical in shape, and the surface is sparse and porous.

[0027] (2) The precursor and the lithium source are mixed uniformly with a Li / Me molar ratio of 1.08:1, then sintered at 740℃ for 12h, and finally a composite oxide powder with Li / Me=1.08 is obtained, which is designated as QL-1. The SEM image of the composite oxide powder is shown in Figure 2. As can be seen from Figure 2, the composite oxide powder obtained after sintering is a single crystal product. EXAMPLES

[0028] (1) Metal mixture (NiO, MgO, ZrO and WO 3 The four metal oxides are mixed in a molar ratio of 1:0.005:0.006:0.004, nitric acid, high purity water, and sodium chloride are added to the reactor in a parallel flow at a molar ratio of 10:1:1:2 to carry out a chemical corrosion crystallization reaction, and 50g / L of ethylenediaminetetraacetic acid is added at the same time. Under normal pressure conditions, the oxidation-reduction potential ORP value is controlled to 100mv, the conductivity is controlled to 500uS / cm, and the stirring input power is 0.7kw / m 3 The reaction time is controlled at 30°C, the metal ion concentration is controlled at 5g / L, the pH value is controlled at 8~10, the reaction temperature is controlled at 60°C, the residence time of the material in the reactor is controlled at 15h, water is consumed continuously during the crystallization process and no excess wastewater is produced, and after the reaction is fully completed, magnetic separation is performed at a magnetic separation intensity of 5000Gas to obtain magnetic particles and slurry, the slurry is separated into solid and liquid to obtain solid particles and filtrate, the solid particles are washed and dried to obtain the precursor, and the magnetic particles, filtrate and washing water are returned to the reactor for further reaction to replenish the water consumed during the crystallization process.

[0029] (2) The precursor and the lithium source were mixed uniformly with a Li / Me molar ratio of 1.06:1, and then calcined at 740°C for 20 h. Finally, a composite oxide powder with Li / Me=1.06 was obtained, which is designated as QL-2. EXAMPLES

[0030] (1) Metal mixture (four kinds of metals, Co, Al, Mn and Ti, mixed in a molar ratio of 1:0.01:0.004:0.005), nitric acid, high purity water and sodium nitrate in a molar ratio of 10:1:1:4 are added to the reactor in parallel flow to carry out chemical corrosion crystallization reaction. At the same time, 30g / L of ammonium nitrate is added. Under normal pressure conditions, the oxidation-reduction potential ORP value is controlled to -200mv, the conductivity is controlled to 1000uS / cm, and the stirring input power is 0.1kw / m 3 The reaction time is controlled at 30°C, the metal ion concentration is controlled at 5g / L, the pH value is controlled at 10~12, the reaction temperature is controlled at 90°C, the residence time of the material in the reactor is controlled at 10h, water is consumed continuously during the crystallization process and no excess wastewater is produced, and after the reaction is fully completed, magnetic separation is performed at a magnetic separation intensity of 2000Gas to obtain magnetic particles and slurry, the slurry is separated into solid and liquid to obtain solid particles and filtrate, the solid particles are washed and dried to obtain the precursor, and the magnetic particles, filtrate and washing water are returned to the reactor for further reaction to replenish the water consumed during the crystallization process.

[0031] (2) The precursor and the lithium source were mixed uniformly with a Li / Me molar ratio of 1.06:1, and then calcined at 960°C for 20 h. Finally, a composite oxide powder with Li / Me=1.06 was obtained, which is designated as QL-3. EXAMPLES

[0032] (1) Metal mixture (five metals of Ni, Co, Al, Zr and Ti are mixed in a molar ratio of 1:0.12:0.15:0.01:0.012), nitric acid, high purity water and sodium sulfate are added to the reactor in a parallel flow at a molar ratio of 10:1:1:1 to carry out a chemical corrosion crystallization reaction. At the same time, 30g / L of ammonium chloride is added. Under normal pressure conditions, the oxidation-reduction potential ORP value is controlled to 100mV, the conductivity is controlled to 5000uS / cm, and the stirring input power is 0.7kw / m 3The reaction time is controlled at 30°C, the metal ion concentration is controlled at 5g / L, the pH value is controlled at 6~8, the reaction temperature is controlled at 60°C, the residence time of the material in the reactor is controlled at 15h, water is consumed continuously during the crystallization process and no excess wastewater is produced, and after the reaction is fully completed, magnetic separation is performed at a magnetic separation intensity of 2000Gas to obtain magnetic particles and slurry, the slurry is separated into solid and liquid to obtain solid particles and filtrate, the solid particles are washed and dried to obtain the precursor, and the magnetic particles, filtrate and washing water are returned to the reactor for further reaction to replenish the water consumed during the crystallization process.

[0033] (2) The precursor and the lithium source were mixed uniformly with a Li / Me molar ratio of 1.05:1, and then calcined at 790°C for 24 h. Finally, a composite oxide powder with Li / Me=1.05 was obtained, which is designated as QL-4. EXAMPLES

[0034] The precursor and the composite oxide powder are produced by the method of Example 1, except that the metal raw material is replaced from a mixture of five metals, Ni, Co, Mn, Zr and W, to a mixture of Ni, Co and Mn in a molar ratio of 1:1:1, and the other conditions are the same as those of Example 1. The precursor and the composite oxide powder with Li / Me=1.08 are obtained. The composite oxide powder is named QL-5. EXAMPLES

[0035] The precursor and the composite oxide powder were produced by the method of Example 1, except that the metal raw material was replaced from a mixture of five metals, Ni, Co, Mn, Zr and W, to a mixture of Ni, Co and Mn in a molar ratio of 5:2:3, and the other conditions were the same as those of Example 1. The precursor and the composite oxide powder with Li / Me=1.08 were obtained. The composite oxide powder was named QL-6. EXAMPLES

[0036] The precursor and the composite oxide powder are produced by the method of Example 1, except that the metal raw material is replaced from a mixture of five metals, Ni, Co, Mn, Zr and W, to a mixture of Ni, Co and Mn in a molar ratio of 10:1:1.5, and the other conditions are the same as those of Example 1. The precursor and the composite oxide powder with Li / Me=1.08 are obtained. The composite oxide powder is named QL-7. EXAMPLES

[0037] The precursor and the composite oxide powder were produced by the method of Example 1, except that the metal raw material was replaced from a mixture of five metals, Ni, Co, Mn, Zr and W, to a mixture of Ni and Co in a molar ratio of 4:1, and the other conditions were the same as those of Example 1. The precursor and the composite oxide powder with Li / Me=1.08 were obtained. The composite oxide powder was named QL-8. EXAMPLES

[0038] The precursor and the composite oxide powder were produced by the method of Example 1, except that the metal raw material was replaced from a mixture of five metals, Ni, Co, Mn, Zr and W, to a mixture of Ni and Mg in a molar ratio of 9.5:0.5, and the other conditions were the same as those of Example 1, and the precursor and the composite oxide powder with Li / Me=1.08 were obtained. The composite oxide powder was named QL-9. Comparative Example 1

[0039] The precursor and the composite oxide powder are produced by the method of Example 5, except that the amount of ammonium sulfate added is 1 g / L, and the other conditions are the same as those of Example 5, and the precursor and the reference composite oxide powder with Li / Me=1.08 are obtained. The reference composite oxide powder is referred to as DQL-1. Comparative Example 2

[0040] The precursor and the composite oxide powder are produced by the method of Example 5, except that the molar ratio of the metal mixture, nitric acid, high purity water, and sodium sulfate is adjusted from 10:1:1:1 to 10:1:1:0.5 to control the electrical conductivity of the system to 100uS / cm, and the other conditions are the same as those of Example 5, and the precursor and the reference composite oxide powder with Li / Me=1.08 are obtained. The reference composite oxide powder is referred to as DQL-2. Comparative Example 3

[0041] The precursor and the composite oxide powder are produced by the method of Example 5, except that the oxidation-reduction potential ORP value is controlled to 150 mv, and the precursor and the reference composite oxide powder with Li / Me=1.08 are obtained. The reference composite oxide powder is referred to as DQL-3. Test Example

[0042] (1) Precursor performance: The particle size, tap density and conformity results are shown in Table 1, where both particle size and conformity are measured using a Malvern laser granulometer.

[0043] (2) Electrochemical performance of lithium-ion batteries: The composite oxide powders obtained in Examples 1 to 9 and the composite oxide powders obtained in Comparative Examples 1 to 3 are used as the positive electrode material. The positive electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) are dissolved in NMP solvent under vacuum conditions in a mass ratio of 80:10:10 to prepare a positive electrode slurry with a solid content of 70% by weight. The positive electrode slurry is applied to a current collector aluminum foil, dried in a vacuum at 120°C for 12 h, and a sheet is punched out to produce a positive electrode wafer with a diameter of 19 mm. The composite modified graphite, CMC, and SBR are dissolved in deionized water under vacuum conditions in a mass ratio of 90:5:5 to prepare a negative electrode slurry with a solid content of 40% by weight. The negative electrode slurry is applied to a current collector copper foil, dried in a vacuum at 100°C for 12 h, and a sheet is punched out to produce a negative electrode wafer with a diameter of 19 mm, and the negative electrode capacity:positive electrode capacity = 1.1:1. The battery is assembled in a glove box filled with argon gas, the assembly sequence is positive electrode case-positive electrode piece-separator-negative electrode piece-stainless steel piece-spring piece-negative electrode case, the electrolyte is 1 mol / L LiPF6 / EC:DMC (volume ratio is 1:1) with 10% (volume fraction) fluoroethylene carbonate (FEC), the separator is a polypropylene microporous membrane, and lithium ion batteries C1-C9 and reference lithium ion batteries DC1-DC3 are obtained. The first discharge performance of the lithium ion batteries C1-C9 and the reference lithium ion batteries DC1-DC3 is tested, and the obtained results are shown in Table 1. [Table 1]

[0044] Although the embodiments of the present invention have been shown and described above, it should be understood that the above embodiments are illustrative and should not be construed as limiting the present invention, and that those skilled in the art may make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention without departing from the principles and spirit of the present invention.

Claims

1. A method for producing a precursor, comprising: subjecting a metal and / or metal oxide, an oxidizing agent, water and a complexing agent to a chemical corrosion crystallization reaction under conditions of electrical conductivity ≧200uS / cm, an oxidation-reduction potential ORP value ≦100mv and a complexing agent concentration of 3-50g / L; the metal and / or metal oxide being at least one selected from the group consisting of nickel, cobalt, manganese, zirconium, tungsten, magnesium, strontium and yttrium, and oxides thereof; magnetically separating the reaction product obtained after the reaction is completed to obtain magnetic particles and a slurry; further subjecting the slurry to solid-liquid separation to obtain solid particles and a filtrate; and then washing and drying the solid particles to obtain the precursor.

2. The use of the oxidizing agent and water converts the metals and / or metal oxides to the corresponding metal hydroxides; 2. The method for producing a precursor according to claim 1, wherein the oxidizing agent is at least one selected from the group consisting of nitric acid, oxygen, air, sodium chlorate, potassium permanganate, and hydrogen peroxide.

3. 3. The method for producing a precursor according to claim 1, wherein the metal and / or metal oxide is at least one selected from the group consisting of Ni-Co-Mn-Zr-W, Ni-Mg-Zr-W, and metal oxides thereof.

4. The electrical conductivity is 200 to 50,000 uS / cm; 2. The method for producing a precursor according to claim 1, wherein the electrical conductivity is controlled by adding a salt to the reaction system, and the salt is at least one selected from sulfates, chlorides, and nitrates of sodium and / or lithium.

5. The chemical corrosion crystallization reaction is a continuous reaction or a batch reaction, The complexing agent is at least one selected from the group consisting of aqueous ammonia, ammonium sulfate, ammonium chloride, ethylenediaminetetraacetic acid, and ammonium nitrate; During the chemical corrosion crystallization reaction process, the stirring intensity is 0.1-1.0 kW / m 2 5. The method for producing a precursor according to claim 1 or 4, characterized in that: the metal ion concentration in the reaction system is 1-30 g / L, the complexing agent concentration is 3-50 g / L, the pH value is 6-12, the reaction temperature is 20-90° C., and the reaction time is 10-150 h.

6. The magnetic separation is a batch type magnetic separation or a continuous type magnetic separation, and the magnetic separation intensity is 100 to 5000 Gas; 2. The method of claim 1, further comprising returning the magnetic particles, the filtrate and the washing water to the chemical corrosion crystallization reaction system to replenish water consumed during the crystallization process.

7. (1) Producing a precursor by the method of claim 1; (2) A method for producing a positive electrode material for a lithium ion battery, comprising: mixing the precursor with a lithium source and then calcining the mixture to obtain a positive electrode material for a lithium ion battery.

8. In step (2), the Li / Me molar ratio of the precursor to the lithium source is (0.9-1.3):1; In step (2), the firing conditions are a temperature of 600 to 1100° C., a time of 5 to 40 hours, and a firing atmosphere of air or oxygen; 8. The method for producing a positive electrode material for a lithium ion battery according to claim 7, wherein in step (2), the lithium source is at least one selected from the group consisting of lithium hydroxide, lithium acetate, lithium nitrate, lithium sulfate and lithium bicarbonate.

Citation Information

Patent Citations

  • Preparation method and application of cathode material for lithium ion battery

    CN104505493A

  • Nickel-manganese composite oxide, method of producing the same, and application thereof

    JP2015110509A